The genetic structure and demographic history revealed by whole-genome resequencing provide insights into conservation of critically endangered Artocarpus nanchuanensis - Xia, Changying; Zuo, Youwei; Xue, Tiantian; Kang, Ming; Zhang, Huan; Zhang, Xiaoxia; Wang, Binru; Zhang, Jiabin; Deng, Hongping (Frontiers in Plant Science, 2023)
Whole-genome resequencing technology covers almost all nucleotide variations in the genome, which makes it possible to carry out conservation genomics research on endangered species at the whole-genome level. In this study, based on the whole-genome resequencing data of 101 critically endangered Artocarpus nanchuanensis individuals, we evaluated the genetic diversity and population structure, inferred the demographic history and genetic load, predicted the potential distributions in the past, present and future, and classified conservation units to propose targeted suggestions for the conservation of this critically endangered species.Whole-genome resequencing for A. nanchuanensis generated approximately 2 Tb of data. Based on abundant mutation sites (25,312,571 single nucleotide polymorphisms sites), we revealed that the average genetic diversity (nucleotide diversity, π) of different populations of A. nanchuanensis was relatively low compared with other trees that have been studied. And we also revealed that the NHZ and QJT populations harboured unique genetic backgrounds and were significantly separated from the other five populations. In addition, positive genetic selective signals, significantly enriched in biological processes related to terpene synthesis, were identified in the 2 NHZ population. The analysis of demographic history of A. nanchuanensis revealed the existence of three genetic bottleneck events. Moreover, abundant genetic loads (48.56% protein-coding genes) were identified in Artocarpus nanchuanensis, especially in genes related to early development and immune function of plants. The predication analysis of suitable habitat areas indicated that the past suitable habitat areas shifted from the north to the south due to global temperature decline. However, in the future, the actual distribution area of A. nanchuanensis will still maintain high suitability. Based on total analyses, we divided the populations of A. nanchuanensis into four conservation units and proposed a number of practical management suggestions for each conservation unit. Overall, our study provides meaningful guidance for the protection of A. nanchuanensis and important insight into conservation genomics research.